Profil Tanggung Jawab Siswa pada Pembelajaran PPKn Kelas IV SD 2 Soco - Kurnia Wijayanti; Yunda Wahyuning Tyas; Ersha Putri Sintiawati; Ervida Eka Aurelya; Fina Fakhriyah; Nur Fajrie (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The aim of this research is to find out and describe the profile of students' responsibilities for PPKn learning for class IV SD 1 Soco. This research uses a quantitative research approach obtained using numbers and data analysis techniques. The sample for this research was all class IV students at SD 1 Soco, totaling 11 students. The research instrument used a questionnaire consisting of 20 questions that measured the level of student responsibility in Civics learning with 4 indicators. The data that has been collected is analyzed using descriptive statistics including percentages. The results of the research show that the level of responsibility of students at SD 1 Soco class IV is mostly in the medium category.